Molecular Characterization of the Asian Tiger Mosquito Aedes albopictus (Skuse) (Diptera: Culicidae) in Northern Italy. (27th March 2013) - Shaikevich, Elena; Talbalaghi, Asghar
Abstract : Polymorphism of the gene COI encoding cytochrome C oxidase subunit I and of the rRNA second internal transcribed spacer (ITS2) was measured in Aedes albopictus collected in three locations in Piedmont region and one location in Liguria region in Italy. According to our data, besides the middle part of the COI gene usually used for analysis, there are also SNPs in the 5′ half of the gene, which can provide additional information about the polymorphism of A. albopictus populations. Based on COI gene, three various mitochondrial haplotypes were identified in A. albopictus from four north Italian sampling sites. Different sources of introductions can be considered. The variability between COI sequences of the north Italian A. albopictus is 0.001 while the variability between them based on the pairwise analysis of ITS2 sequences is 10 time more—0.011. For the first time, a 4% divergence between the populations of A. albopictus of tropical and subtropical origins was found on the basis of analyzing the ITS2. A relatively high level of variability of ITS2 between tropical and subtropical populations can be used to develop new markers for phylogenetic studies. No individuals with mitochondrial and nuclear haplotypes specific to tropical populations were found in the four north Italian sampling sites.